Mass Production of Microalgae - Pires, JCM (2015)
Microalgae are photosynthetic microorganisms that can be found in diverse natural environments, such as water, rocks, and soil. They present higher photosynthetic efficiency than terrestrial plants, and are responsible for a significant fraction of the world oxygen production. The high growth rate attributed to microalgae gives them irrefutable economic potential. Besides the production of high-value products (for human and animal nutrition, cosmetics, and pharmaceuticals), they have recently been studied for some environmental and energy applications: (1) CO2 capture; (2) bioenergy production; and (3) nutrient removal from wastewater. However, none of these applications are economically viable, mainly due to the requirements of water, nutrients, and energy. Thus, this chapter gives an overview of all steps of the microalgal production chain, presenting a variety of research advances.